FLORA GUNUNG KELIMUTU DAN GUNUNG KELIBARA TAMAN NASIONAL KELIMUTU, PULAU FLORES, NUSA TENGGARA TIMUR - Wiriadinata, Harry; Wawo, Albert H (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Flora of Mt Kelimutu and Mt Kelibara, Kelimutu National Park, Flores, Lesser Sunda Islands had been studied in July-August 2007.About 70 species belongs to 67 families of plants were collected. Vegetation is dominated by Casuarina junghuhniana Eucalyptus urophylla forest and mixed mountain forest composed of e.q. Ficus variegata, Prunus arborea, Actinodaphne glomerata, Litsea resinosa, Celtis tetrandra and Engelhardtia spicata. It is very interesting due it has many endemic species such as Agalmyla elongata, Calamus heteracanthus, Saurauia schmutzii and S. verheijernii those are endemic to Flores island and Rhododendron renschianum which is endemic in the Kelimutu National Park. During the exploration a new species of Begonia kelimutuensis (in preparation) was recorded.